New World A-Coming: Black Religion and Racial Identity during the Great Migration - Weisenfeld, Judith (New York University Press, 2017)
Frontmatter -- Contents -- Acknowledgments -- List of abbreviations -- Introduction -- 1. Geographies of race and religion -- 2. Sacred time and divine histories -- 3. Religio- racial self- fashioning -- 4. Maintaining the religio- racial body -- 5. Making the religio- racial family -- 6. The religio- racial politics of space and place -- 7. Community, conflict, and the boundaries of black religion -- Conclusion -- Notes -- Select bibliography -- Index -- About the author